INTERFACE BETWEEN HEALTHCARE REGULATION AND EQUITY: AN INTEGRATIVE REVIEW OF THE LITERATURE - Caroline Cechinel Peiter; Gabriela Marcellino de Melo Lanzoni; Walter Ferreira de Oliveira (Universidade Federal do Paraná, 2017)
This article aims to present the interface between Healthcare Regulation and the principle of equity, according to the scientific literature from the area of health, from 2008 to 2015. It is an integrative review of the literature, based on two databases, undertaken in June 2016. A total of 15 studies which met the inclusion criteria were analyzed. The knowledge was summarized in two categories of analysis: 1) "Equity and Access" and 2) "Reform of health systems". Healthcare Regulation is understood as an important instrument for promoting equity. The health services must prioritize the attendance of service users with greater risks, allowing all to have adequate levels of health, based on the offering of distinct services, according to individual needs. Issues such as equity, access and financing were strong points considered in the processes of reform of health systems.